PERTUMBUHAN DAN PRODUKSI POLONG SEGAR EDAMAME VARIETAS RIOKOPADA EMPAT JENIS PUPUK - Jaenudin Kartahadimaja; Risa Wentasari; Rizka Novi Sesanti (Universitas Trunojoyo Madura, 2010)
The use of multiple kinds of fertilizers on edamame plants have been conducted in Lampung State Polytechnic aims to see the growth and yield of fresh edamame pods varieties of Rioko are planted using four different types of fertilizer. The experiment was arranged in a randomized complete block design. Treatments consisted of four kinds of fertilizers, ie P1 = cow dung manure 20 ton.ha -1, P2 = chemical fertilizers (100 kg Urea.ha-1 + 150 kg SP36.ha-1 + 150 kg KCl.ha-1) ; P3 = 100 kg Urea.ha-1 + 150 kg SP36.ha-1 + 150 kg KCl.ha-1 + 20 ton.ha-1 cow dung; and P4 = Fertilizer Nadira 12 ton.ha-1. Each treatment was repeated three times. Data were analyzed by variance. If there are differences among the treatments used is followed by Least Significant Difference Test (LSD) at 5% level. The results show the four types of fertilizer used is not significantly increased plant height, number of pods per plant, weight of 100 grains of fresh seed and pod weight per plant, but significantly increased the number of branches per plant. Cow manure 20 ton.ha-1 performed better than 12 ton.ha Nadira-1 and combination of chemical fertilizer + manure.